ASSESSING LEAN AND GREEN COEXISTENCE, AN APPROACH BASED ON TRIZ AND DISCRETE EVENT SIMULATION TECHNIQUE - Essaber, Fatima Ezzahra; Benmoussa, Rachid; De Guio, Roland; Ben Moussa, Fatima Zahra (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Nowadays, Lean supply chain managers are seeking Green implementation, which is no longer a choice but an obligation; to comply with government regulations about the environmental footprint, to preserve the image, and to satisfy customers. Although several research works have been conducted in the framework of Lean and Green, the relationship between both paradigms remains ambiguous at a conceptual level. The purpose of this research work is to provide managers and decision-makers with a formal, relevant, and generalizable approach that explicit how to accurately assess Lean and Green coexistence. We propose the approach based on the Theory of Inventive Problem Solving (TRIZ) and Discrete Event Simulation technique (DES). Integrating this technique amounts to its ability to describe complex systems and their performance. Besides, DES is time-saving, cost-saving, and labor-saving. An academic case study is presented in order to demonstrate the applicability of the proposed approach. The deployment of the approach revealed that Lean and Green aspects could be the antagonist. Indeed, thinking Green is not necessarily Lean and vice versa, which supports that Lean Green supply chain challenges may surpass classic optimization techniques and methods; hence, its management requires innovative approaches. In this setting, our findings highlight the importance of integrating TRIZ. The developed framework in this research work stands out for its simplicity, flexibility, and generalizability.